Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's solve the inequality step by step.
### Given Inequality:
[tex]\[ -\frac{3}{4} x - 6 \leq 18 \][/tex]
### Step 1: Isolate the term involving [tex]\( x \)[/tex]
First, we need to get rid of the constant term on the left-hand side. We can do this by adding 6 to both sides of the inequality:
[tex]\[ -\frac{3}{4} x - 6 + 6 \leq 18 + 6 \][/tex]
[tex]\[ -\frac{3}{4} x \leq 24 \][/tex]
### Step 2: Eliminate the fraction
Now, we need to eliminate the fraction. We can do this by multiplying both sides by the reciprocal of [tex]\(-\frac{3}{4}\)[/tex], which is [tex]\(-\frac{4}{3}\)[/tex]. When we multiply both sides by a negative number, we must reverse the inequality sign:
[tex]\[ x \geq 24 \times \left(-\frac{4}{3}\right) \][/tex]
[tex]\[ x \geq 24 \times -\frac{4}{3} \][/tex]
[tex]\[ x \geq -32 \][/tex]
So, the inequality simplifies to:
[tex]\[ x \geq -32 \][/tex]
### Interpretation with the given conditions:
Now we analyze the given conditions to determine which ones satisfy [tex]\( x \geq -32 \)[/tex].
- [tex]\( x \geq -32 \)[/tex]
- [tex]\( x \geq -18 \)[/tex]
- [tex]\( x \geq -16 \)[/tex]
- [tex]\( x \geq -9 \)[/tex]
Since [tex]\( x \geq -32 \)[/tex] encompasses all the other conditions (as they are greater than [tex]\(-32\)[/tex]), the broadest solution set for [tex]\( x \)[/tex] is:
[tex]\[ x \geq -32 \][/tex]
Hence, the solution to the inequality and the appropriate range from the given conditions is:
[tex]\[ x \geq -32 \][/tex]
So, the inequality [tex]\( -\frac{3}{4} x - 6 \leq 18 \)[/tex] holds true for [tex]\( x \geq -32 \)[/tex].
### Given Inequality:
[tex]\[ -\frac{3}{4} x - 6 \leq 18 \][/tex]
### Step 1: Isolate the term involving [tex]\( x \)[/tex]
First, we need to get rid of the constant term on the left-hand side. We can do this by adding 6 to both sides of the inequality:
[tex]\[ -\frac{3}{4} x - 6 + 6 \leq 18 + 6 \][/tex]
[tex]\[ -\frac{3}{4} x \leq 24 \][/tex]
### Step 2: Eliminate the fraction
Now, we need to eliminate the fraction. We can do this by multiplying both sides by the reciprocal of [tex]\(-\frac{3}{4}\)[/tex], which is [tex]\(-\frac{4}{3}\)[/tex]. When we multiply both sides by a negative number, we must reverse the inequality sign:
[tex]\[ x \geq 24 \times \left(-\frac{4}{3}\right) \][/tex]
[tex]\[ x \geq 24 \times -\frac{4}{3} \][/tex]
[tex]\[ x \geq -32 \][/tex]
So, the inequality simplifies to:
[tex]\[ x \geq -32 \][/tex]
### Interpretation with the given conditions:
Now we analyze the given conditions to determine which ones satisfy [tex]\( x \geq -32 \)[/tex].
- [tex]\( x \geq -32 \)[/tex]
- [tex]\( x \geq -18 \)[/tex]
- [tex]\( x \geq -16 \)[/tex]
- [tex]\( x \geq -9 \)[/tex]
Since [tex]\( x \geq -32 \)[/tex] encompasses all the other conditions (as they are greater than [tex]\(-32\)[/tex]), the broadest solution set for [tex]\( x \)[/tex] is:
[tex]\[ x \geq -32 \][/tex]
Hence, the solution to the inequality and the appropriate range from the given conditions is:
[tex]\[ x \geq -32 \][/tex]
So, the inequality [tex]\( -\frac{3}{4} x - 6 \leq 18 \)[/tex] holds true for [tex]\( x \geq -32 \)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.